Supplementing a yeast-derived product to enhance productive and health responses of beef steers. (26th December 2017) - Silva, L. G. T.; Cooke, R. F.; Schubach, K. M.; Brandão, A. P.; Marques, R. S.; Schumaher, T. F.; Moriel, P.; Bohnert, D. W.
Abstract : This experiment evaluated the impacts of supplementing a yeast-derived product (Celmanax; Church & Dwight Co., Inc., Princeton, NJ, USA) on productive and health responses of beef steers, and was divided into a preconditioning (days 4 to 30) and feedlot receiving phase (days 31 to 69). In all, 84 Angus × Hereford steers were weaned on day 0 (BW=245±2 kg; age=186±2 days), and maintained in a single group from days 0 to 3. On day 4, steers were allocated according to weaning BW and age to a 21-pen drylot (4 steers/pen). Pens were randomly assigned to ( n =7 pens/treatment): (1) no Celmanax supplementation during the study, (2) Celmanax supplementation (14 g/steer daily; as-fed) from days 14 to 69 or (3) Celmanax supplementation (14 g/steer daily; as-fed) from days 31 to 69. Steers had free-choice access to grass-alfalfa hay, and were also offered a corn-based concentrate beginning on day 14. Celmanax was mixed daily with the concentrate. On day 30, steers were road-transported for 1500 km (24 h). On day 31, steers returned to their original pens for the 38-day feedlot receiving. Shrunk BW was recorded on days 4, 31 and 70. Feed intake was evaluated daily (days 14 to 69). Steers were observed daily (days 4 to 69) for bovine respiratory disease (BRD) signs. Blood samples were collected on days 14, 30, 31, 33, 35, 40, 45, 54 and 69, and analyzed for plasma cortisol, haptoglobin, IGF-I, and serum fatty acids. Preconditioning results were analyzed by comparing pens that received (CELM) or not (CONPC) Celmanax during the preconditioning phase. Feedlot receiving results were analyzed by comparing pens that received Celmanax from days 14 to 69 (CELPREC), days 31 to 69 (CELRECV) or no Celmanax supplementation (CON). During preconditioning, BRD incidence was less ( P =0.03) in CELM v . CONPC. During feedlot receiving, average daily gain (ADG) ( P =0.07) and feed efficiency ( P =0.08) tended to be greater in CELPREC and CELRECV v . CON, whereas dry matter intake was similar ( P ⩾0.29) among treatments. No other treatment effects were detected ( P ⩾0.20). Collectively, Celmanax supplementation reduced BRD incidence during the 30-day preconditioning. Moreover, supplementing Celmanax tended to improve ADG and feed efficiency during the 38-day feedlot receiving, independently of whether supplementation began during preconditioning or after feedlot entry. These results suggest that Celmanax supplementation benefits preconditioning health and feedlot receiving performance in beef cattle.